Persepsi Kemudahan, Persepsi Manfaat, dan Persepsi Risiko Terhadap Penggunaan Kembali Shopeepay (Studi Kasus SMK NU Gresik) - Susilo Aji; Erika Widia Ningtyas (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2025)
ShopeePay is a form of service e-wallet from Shopee, which is one of the electronic money services that is widely used by the public, which based on a survey conducted by UMN Consulting stated that as many as 42.77 percent of its users were in the age range 1-17 years. Therefore, the object of this research is SMK NU Gresik. Meanwhile, the subjects of this research were NU Gresik Vocational School students, using a purposive sampling technique, the sample in this research consisted of 88 respondents. To carry out data analysis in this study, multiple linear regression analysis was used with the SPSS 25 application. The test results show that perceived convenience, perceived benefits and perceived risk have a positive and significant effect on the reuse of Shopeepay (Case Study of SMK NU Gresik).